Reasserting the Buddhist tradition: Lü Bicheng and Chinese vegetarianism in a global context - Schumann, Matthias (Twentieth-Century China, 2024)
Examining the transnational activities of the famous poetess, journalist, and Pure Land Buddhist Lü Bicheng (1883-1943), this article explores how the Buddhist practices of vegetarianism and nonkilling were transformed during the early twentieth century within an increasingly globalized religious sphere. Lü traveled widely through Europe and North America, and, in her English-language writings and lectures, she presented vegetarianism and nonkilling not only as essential aspects of Buddhist practice but also as forces of social and political reform. Engaging with Buddhists and animal protection activists from around the world, she aimed to spread a more positive image of Chinese Pure Land Buddhism, which was marginalized in international discourses of the time. The activities of Lü Bicheng thereby show how Chinese Buddhists aimed to project their own ideas onto the global stage and became active voices in a global "coproduction" of Buddhist knowledge.